Interaction Affinity Between Flavonoids Against Cytokines Interleukin 12 in Diabetes Mellitus - Wuryandari, MM. Riyaniarti Estri; Yuliati, Ninis; Sutikno, Ekawati; Mohamed, Saad A (MEDIA ILMU KESEHATAN, 2023)
Background: Interleukin 12 can destroy insulin-producing cells, suppresses IL4 production, and can stimulate the formation of Thelper1. Quercetin is a flavonoid suitable to be chosen as the lead compound for development of safe anti-diabetic agent because in addition to its anti-diabetic effect, quercetin shows also protective effect in pancreas track.Objective: This research aims to study the docking models of certain flavonoids and to predict the quercetin and triterpene derivatives inhibition activity on Interleukin12.Method: The molecular docking method was used using the PyRx program with the Autodock Vina menu.Results: IL-12 bond affinity with Dextromethoorpene results -7 kcal/mol as the highest affinity value energy while the lowest energy is -6.1 kcal/mol, IL-12 bond affinity value with Quercetin with the highest affinity value energy is -9 kcal/mol, and the lowest energy is -7.8kcal/mol. The affinity value IL-12 bond and triterpene with the highest affinity value is energy -7 .9 kcal/mol, and the lowest energy is -7.4 kcal/molConclusion: Quercetin, has hydrogen bonds and hydrophobic bonds, where the ligand of the Quercetin compound is the ligand that has the ability to form the best interactions and bonds with IL-12 receptors (4OG9)